Non-Surgical Retreatment of Maxillary Lateral Incisor with Unusual Anatomy: A Case Report and Mini Review - Shubbar, Ashraf; Bolhari, Behnam; Fakhari, Nooshin; Alemi, Parvin; Nosrat, Ali (Iranian Endodontic Journal, 2017)
Knowledge about internal anatomy plays a crucial role in the success of the root canal treatment. Many studies on internal anatomy have repeatedly reported that maxillary lateral incisors have only one canal. The primary aim of this article was to describe successful non-surgical retreatment of a permanent maxillary lateral incisor with two root canals and open apices. The treatment was carried out using dental operating microscope and the canals were obturated with mineral trioxide aggregate (MTA) as an apical plug. A review of literature was also conducted to evaluate the anatomical variations of maxillary lateral incisors. Keywords: Maxillary Lateral Incisor; Retreatment; Root Canal Anatomy